Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Konsumen Sakhi’s Coffee & Resto Di Kota Medan - Adelina Lubis; Sari Bulan Tambunan; Muslim Wijaya (Mahesa Research Center, 2021)
The sample in this study were 100 people consumers. The analytical technique used in this study is descriptive analysis and multiple linear regression test. The results of this study indicate that the product quality variable partially has a positive and significant effect on consumer satisfaction, the service quality variable partially has a positive and significant effect on customer satisfaction. consumer satisfaction, the price variable partially has a positive and significant effect on consumer satisfaction. The Adjusted R Square value obtained is 0.363 this figure shows that it is 36.3%. Consumer satisfaction (the dependent variable) can be explained by the variables of product quality, service quality and price. The remaining 63.7% is influenced by other factors not described in this study.